2021
DOI: 10.3390/ijms221810054
|View full text |Cite
|
Sign up to set email alerts
|

Antistress Action of Melanocortin Derivatives Associated with Correction of Gene Expression Patterns in the Hippocampus of Male Rats Following Acute Stress

Abstract: Natural melanocortins (MCs) have been used in the successful development of drugs with neuroprotective properties. Here, we studied the behavioral effects and molecular genetic mechanisms of two synthetic MC derivatives-ACTH(4–7)PGP (Semax) and ACTH(6–9)PGP under normal and acute restraint stress (ARS) conditions. Administration of Semax or ACTH(6–9)PGP (100 μg/kg) to rats 30 min before ARS attenuated ARS-induced behavioral alterations. Using high-throughput RNA sequencing (RNA-Seq), we identified 1359 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…It was shown that the phospholipase A2 activity induced by Pla-family genes was associated not only with ischemic stroke but also with Alzheimer's disease and vascular dementia [39]. Moreover, the Pla2g3 gene was included in the top five upregulated genes in the rat hippocampus in response to acute stress [40]. Previous studies have shown that the anti-inflammatory S-2474 drug rescues cortical neurons from human group IIA secretory phospholipase A(2)-induced apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that the phospholipase A2 activity induced by Pla-family genes was associated not only with ischemic stroke but also with Alzheimer's disease and vascular dementia [39]. Moreover, the Pla2g3 gene was included in the top five upregulated genes in the rat hippocampus in response to acute stress [40]. Previous studies have shown that the anti-inflammatory S-2474 drug rescues cortical neurons from human group IIA secretory phospholipase A(2)-induced apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated as previously described [40]. RNA integrity was checked using capillary electrophoresis (Experion, BioRad, Hercules, CA, USA).…”
Section: Rna Isolationmentioning
confidence: 99%
See 3 more Smart Citations